Partial MHC class II constructs inhibit MIF/CD74 binding and downstream effects - Benedek, Gil; Meza‐Romero, Roberto; Andrew, Shayne; Leng, Lin; Burrows, Gregory G.; Bourdette, Dennis; Offner, Halina; Bucala, Richard; Vandenbark, Arthur A. (European journal of immunology, 2013)
MIF and its receptor, CD74, are pivotal regulators of the immune system. Here, we demonstrate for the first time that partial MHC class II constructs comprised of linked β1α1 domains with covalently attached antigenic peptides (also referred to as recombinant T‐cell receptor ligands — RTLs) can inhibit MIF activity by not only blocking the binding of rhMIF to immunopurified CD74, but also downregulating CD74 cell‐surface expression. This bifunctional inhibition of MIF/CD74 interactions blocked downstream MIF effects, including enhanced secretion of proinflammatory cytokines, anti‐apoptotic activity, and inhibition of random migration that all contribute to the reversal of clinical and histological signs of EAE. Moreover, we demonstrate that enhanced CD74 cell‐surface expression on monocytes in mice with EAE and subjects with multiple sclerosis can be downregulated by humanized RTLs, resulting in reduced MIF binding to the cells. Thus, binding of partial MHC complexes to CD74 blocks both the accessibility and availability of CD74 for MIF binding and downstream inflammatory activity.